ANALISIS VALUE AT RISK PORTOFOLIO SAHAM LQ45 DENGAN METODE SIMULASI MONTE CARLO CONTROL VARIATES - Westi Widiyatari; Evy Sulistianingsih; Wirda Andani (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2023)
Value at Risk (VaR) with the Monte Carlo (MC) simulation is an estimate of the maximum loss over a given period of time and with a specific degree of confidence. MC VaR uses the Control Variates (CV) technique which is one of the reduction techniques in the MC method to improve the efficiency of VaR estimation. This study also aims to analyze the risk of the LQ45 indexed stock portofolio with Monte Carlo Control Variates (MCCV) VaR. In addition, this study compares MCCV VaR with standar MC VaR. The closing prices of the shares of PT Bank Negara Indonesia Tbk (BBNI) and PT Bank Central Asia Tbk (BBCA) were the source of the data for this study. The 95% confidence level is used for this study to estimate one-day MCCV VaR. The results obtained show that MCCV is able to reduce the variance of the estimate more quickly than the standar MC VaR. Thus, MCCV VaR is more efficient than the standard MC VaR.